Revistas culturales y redes intelectuales: una aproximación metodológica - Pita, Alexandra (2014)
This article discusses the ways to approach, as well the devices that allow us to deepen the analysis of intellectual magazines, taking these publications not as a documental source that serves only for support, but as an object of autonomous study. Therefore, the discussion focuses on the Latin American intellectual journals of the first half of XX century in order to propose a methodological approach that allows the complex study of the publication and with the intellectual networks that gave them life. The way to make this proposal is carried through two successive approximations that allow at first moment, the analysis of the most general features that allow us to define the profile and personality of the cultural magazine and a second address to the study of particular variables grouped by study categories.